2020
DOI: 10.1002/jbio.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing near‐infrared spectroscopy signal under hypercapnia

Abstract: Vasoactive stress tests (i.e. hypercapnia, elevated partial pressure of arterial CO 2 [PaCO 2 ]) are commonly used in functional MRI (fMRI), to induce cerebral blood flow changes and expose hidden perfusion deficits in the brain. Compared with fMRI, near-infrared spectroscopy (NIRS) is an alternative low-cost, real-time, and non-invasive tool, which can be applied in out-of-hospital settings. To develop and optimize vasoactive stress tests for NIRS, several hypercapniainduced tasks were tested using concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…This statement is further supported by the fact that during cognitive tasks HbR has higher correlation with BOLD-fMRI than HbO or HbT 108 . Higher correlations between HbR and BOLD-fMRI during CO 2 tasks have also been reported 71 , 99 . However, due to its low dynamic range, HbR is more prone to motion artifacts and therefore results in an underestimation of hemodynamic activity associated with NVC or CVR 30 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This statement is further supported by the fact that during cognitive tasks HbR has higher correlation with BOLD-fMRI than HbO or HbT 108 . Higher correlations between HbR and BOLD-fMRI during CO 2 tasks have also been reported 71 , 99 . However, due to its low dynamic range, HbR is more prone to motion artifacts and therefore results in an underestimation of hemodynamic activity associated with NVC or CVR 30 .…”
Section: Discussionmentioning
confidence: 71%
“…However, presence of SBF during the hypercapnic task is surprising, since studies have reported that PaCO 2 does not induce SBF changes 23 , 97 . A possible explanation underlying such findings may be that SBF changes in extracerebral layers are temporally delayed, rather than minimal or not present 98 , 99 . In cognitive tasks, systemic activities such as myogenic, respiratory and cardiac oscillations were found to have higher contributions in the short-SDS measurements than the long-SDS measurements (see Post-hoc SDS columns of Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This statement is further supported by the fact that during cognitive tasks HbR has higher correlation with BOLD-fMRI than HbO or HbT 108 . Higher correlations between HbR and BOLD-fMRI during CO2 tasks have also been reported 71,99 . However, due to its low dynamic range, HbR is more prone to motion artifacts and therefore results in an underestimation of hemodynamic activity associated with NVC or CVR 30 .…”
Section: Discussionmentioning
confidence: 71%
“…However, presence of SBF during the hypercapnic task is surprising, since studies have reported that PaCO2 doesn't induce SBF changes 23,97 . A possible explanation behind such findings may be that SBF changes in extracerebral layers are temporally delayed, rather than minimal or not present 98,99 . In cognitive tasks, systemic activities such as myogenic, respiratory and cardiac oscillations were found to have higher contributions in the short-SDS measurements than the long-SDS measurements (see Post-hoc SDS columns of Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility remains largely overlooked but is particularly insidious when analyzing tasks associated with autonomic activations, that may profoundly affect the circulation in cutaneous tissues of the head. This confounding factor has been held responsible for inconsistent effects of CO2 challenges on B-L NIRS variables [63]. Conversely, the SRS variables were shown to be quite independent of extracranial circulation, providing consistent changes in response to hyperventilation and rebreathing [64,65].…”
Section: Repeated Measures Anovamentioning
confidence: 99%